STRUCTURAL AND BIODIVERSITY CHARACTERISTICS OF NATURAL FORESTS IN MUONG PHANG HISTORICAL MONUMENT, DIEN BIEN PROVINCE - Thi Bich Phuong, Nguyen; Thi Hoa, Doan (Journal of Forestry Science and Technology, 2018)
Forest ecosystem of the Historical and Environmental Landscape Muong Phang is located in Muong Phang Commune and Pa Khoang Commune, Dien Bien district, Dien Bien province which is a tropical moist broadleaf forest. The studied results on 9 plots with the area of 2,500m2 in IIA, IIB and IIIA2 showed that the composition of canopy layers is diversified, in which state IIA consists of 10 species with average density 291 trees/ha, state IIB has an average density of 303 trees/ha including 13 species; state IIIA2 encompasses 18 species with density of 209 trees/ha. State IIB and IIIA2 have three main canopy layers A1, A2 and A3 with crown cover of 0.52 and 0.61, respectively, while state IIA has two main storeys A2, A3 with crown cover of 0.45. In particular, the highest species diversity belongs to state IIIA2. Diameter and height of canopy layers are significantly different between three forest states expressed in Sig. value < 0.05. Regeneration density ranges from 828 trees/ha in state IIA to 995 trees/ha in state IIIA2. Species diversity of regeneration layers under state IIIA2 is the highest in three states.